The Role of Land Use Types and Water Chemical Properties in Structuring the Microbiomes of a Connected Lake System - Marmen, Sophi; Blank, Lior; Al-Ashhab, Ashraf; Malik, Assaf; Ganzert, Lars; Lalzar, Maya; Grossart, Hans-Peter; Sher, Daniel (Frontiers in Microbiology, 2020)
Lakes and other freshwater bodies are intimately connected to the surrounding land, yet to what extent land-use affects the quality of freshwater and the microbial communities living in various freshwater environments is largely unknown. We address this question through an analysis of the land use surrounding 46 inter-connected lakes located within 7 different drainage basins in northern Germany, and the microbiomes of these lakes during early summer. Lake microbiome structure was not correlated with the specific drainage basin or by basin size, and bacterial distribution did not seem to be limited by distance. Instead, land use within the drainage basin could predict, to some extent, NO2+NO3 concentrations in the water, which (together with temperature, chlorophyll a and total phosphorus) correlated to some extent with the water microbiome structure. Land use directly surrounding the water bodies, however, had little observable effects on water quality or the microbiome. Several microbial lineages, including Cyanobacteria and Verrucomicrobia, were differentially partitioned between the lakes. Significantly more data, including time-series measurements of land use and water chemical properties, are needed to fully understand the interaction between the environment and the organization of microbial communities.